Effect of Lepidium sativum L. (Garden Cress) Seed and Its Extract on Experimental Eimeria tenella Infection in Broiler Chickens - Adamu, Meskerem; Boonkaewwan, Chaiwat (Agriculture and Natural Resources, 2014)
The anticoccidial effects of Lepidium sativum (LS) seed were assessed on 240, male, broiler chickens aged 1 d following oral inoculation of 1 × 105 sporulated E. tenella oocysts. The experimental study was conducted at the Debre Zeit Agricultural Research Center Poultry Farm. LS was included in the feed of the chickens in the form of seed powder, whole seed or extract. Broiler chickens were assigned to eight treatments: noninfected and unsupplemented (control check), infected and unsupplemented (control), infected and supplemented with seed powder, whole seed, extract or amprolium and noninfected and supplemented with seed powder or whole seed. One g.kg-1 of each seed preparation in feed was applied. Treatments were applied for a period of 2 wk from day 18 of hatching. Treatment efficacy was assessed based on measuring and the analysis of the parameters: 1) performance measures (body weight gain, feed intake, mortality); 2) fecal oocysts measurements; and 3) intestinal lesion scores. The body weight gains of E. tenella-challenged chickens fed LS-supplemented diets were significantly (P < 0.003) higher than those fed the control diet. Chickens fed the LS-supplemented diet following E. tenella infection demonstrated a significantly higher reduction of mortality (P < 0.0001), fecal oocyst shed (P < 0.0007) and lesion score (P < 0.0001) than those fed the unsupplemented or control diet. However, noninfected chickens fed seed powder of the LS-supplemented diet showed lesion scores and mortality. Lepidium sativum-supplemented diets demonstrated effective anticoccidial results on E. tenella-challenged chickens.